Pengaruh Capital Intensity, Profitabilitas terhadap Tax Avoidance dengan Kepemilikan Institusional sebagai Variabel Moderasi: Studi Kasus Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Kinasih, Estu; Nuryati, Tutty; Rosa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The aim of this research is to determine the relationship between variables through hypothesis testing, in order to obtain research results. This type of research is causal or the relationship of cause and effect with a quantitative approach. The sampling technique in this research used purposive sampling. The results of this research show that capital intensity and profitability have a positive effect on tax avoidance. Institutional ownership as a moderating variable is able to moderate capital intensity and profitability on tax avoidance.